Multi Channel Network Trend in Indonesia (Case Study Podkesmas & Close the Door) - Eko Sopian; Firza Priyanda Zahir; Catheline Karen Wowiling (Green Publisher Indonesia, 2024)
This article explores the trend of Multi Channel Network (MCN) in Indonesia through the case studies of Podkesmas on Spotify and Close The Door on YouTube. The study uses a qualitative descriptive approach with data collected through document analysis and interpretive methods to examine how MCNs support content creators in expanding audience reach and monetization strategies. Findings reveal that Podkesmas has achieved over 35 million plays by collaborating with major brands, while Close The Door leverages a collaborative ecosystem to strengthen brand equity and attract broader audiences. The study concludes that MCNs play a crucial role in enhancing content creators’ branding and monetization in Indonesia’s digital media landscape. Future research is recommended to investigate MCNs on other platforms, analyze audience behavior more deeply, and develop localized strategies for optimizing MCN collaboration.